A Burst of Numt Insertion in the Dasyuridae Family During Marsupial Evolution - Hazkani-Covo, Einat (Frontiers in Ecology and Evolution, 2022)
Nuclear pseudogenes of mitochondrial origin (numts) are common in all eukaryotes. Our previous scan of numts in sequenced nuclear genomes suggested that the highest numt content currently known in animals is that in the gray short-tailed opossum. The present work sought to determine numt content in marsupials and to compare it to those in placental and monothematic mammals as well as in non-mammalian vertebrates. To achieve this, 70 vertebrate species with available nuclear and mitochondrial genomes were scanned for numt content. An extreme numt content was found in the Dasyuridae, with 3,450 in Sarcophilus harrisii (1,955 kb) and 2,813 in Antechinus flavipes (847 kb). The evolutionarily closest species analyzed, the extinct Thylacinus cynocephalus belonging to the Thylacindae family, had only 435 numts (238 kb). These two Dasyuridae genomes featured the highest numt content identified in animals to date. A phylogenetic analysis of numts longer than 300 bp, using a Diprotodonita mitochondrial tree, indicated a burst of numt insertion that began before the divergence of the Dasyurini and Phascogaline, reaching a peak in the early evolution of the two tribes. No comparable increase was found in the early divergent species T. cynocephalus. Divergence of the Dasyuridae tribes has been previously dated to shortly after the Miocene climate transition, characterized by a rapid temperature decline. Interestingly, deviation from optimal growth temperature is one of the environmental factors reported to increase numt insertions in a laboratory setting.